Total Arsenic, pH, and Sulfate Are the Main Environmental Factors Affecting the Microbial Ecology of the Water and Sediments in Hulun Lake, China - Shang, Yongquan; Wu, Xiaoyang; Wei, Qinguo; Dou, Huashan; Wang, Xibao; Chen, Jun; Zhang, Huanxin; Ma, Shengchao; Zhang, Honghai (Frontiers in Microbiology, 2020)
Bacteria have the metabolic potential to produce a diverse array of secondary metabolites, which have important roles in biogeochemical cycling processes. However, for Hulun Lake and the rivers that enter into it, the bacterial community structures and their effects have not previously been widely studied, limiting our ecological understanding of this habitat. To address this, we have analyzed the bacterial communities in the water ecosystem of the Hulun lake basin. 16S rRNA high-throughput sequencing identified 64 phylum, 165 classes, 218 orders, 386 families, and 740 genera of bacteria, across all samples. The dominant phyla in the central area of the lake were Proteobacteria, Actinobacteria, Firmicutes, and Cyanobacteria, while in all other areas Proteobacteria, Actinobacteria, and Bacteroidetes were dominant. The microbial community structures were significantly affected by environmental factors (As, pH, and SO42-) and their location in the lake. The species richness in the sediments of Hulun Lake was higher than in the water, and this ecosystem harbored the highest proportion of unclassified sequences, representing unclassified bacteria. This study provides basic data for future investigations into the Hulun lake ecosystem, and for water microbial monitoring and protection measures.